Americanization of history : conflation of time and culture in film and television - McDonald, Kathleen (Kathleen A.) (Cambridge Scholars, 2011)
This collection of essays searches for how history and literature translate into filmic texts reflecting the time and place of the translation. Major motion pictures as well as television movies and series are the sites of this exploration. The opening essay surveys what films tell us it means to be set in a medieval time, while the second looks at one of the most powerful movie studios since the earliest days of movie-making, Walt Disney Studios. The second section investigates classic Ameri ...